Pilot study on a new concept of documenting the clinical relevance of patch test results in contact dermatitis patients. (23rd August 2018) - Uter, Wolfgang; Bauer, Andrea; Bensefa‐Colas, Lynda; Brans, Richard; Crépy, Marie‐Noëlle; Giménez‐Arnau, Ana; Larese Filon, Francesca; Ljubojević Hadžavdić, Suzana; Pesonen, Maria; Schuttelaar, Marie L.A.; Wilkinson, Mark
Abstract : Background: Assessment of the clinical relevance of patch test reactions is an essential part of the diagnostic work‐up of patients with (occupational) contact dermatitis. However, final diagnostic information, particularly the clinical relevance of allergic patch test reactions, has hitherto been ill‐represented in clinical documentation systems (patch test software) and surveillance registries based on these. Objectives: To develop, implement as a pilot study, and analyse concerning feasibility and contents a new concept of representing the full scope of diagnostic information utilized in the diagnosis of patients with (occupational) contact dermatitis. Methods: On the basis of a European working group discussion on items to document and catalogue lists to use for this purpose, an online documentation system to collect data was set up, followed by pilot use involving 9 dermatology departments across Europe. Results: Data on 176 patients with suspected occupational hand dermatitis were included; among these, work‐relatedness was confirmed in 150, and in 53 non‐occupational aetiology was the sole or a contributory cause. Data were further analysed with regard to occupations, product categories, substances (haptens), source of information on which the evaluation was based, and various combinations of these factors, to illustrate the usefulness of the proposed data representation. Conclusions: An improved method of data collection is presented that more accurately links allergen to exposure and to clinical disease and patient history, and thus better represents clinical relevance. This enables more precise analysis of the causation of contact dermatitis, occupational or non‐occupational, and thereby better targeting of prevention. The development of future databases should incorporate the above considerations to record the results of investigation. Abstract :